Modern Times : Responding to chaos - Becker, Lutz; Wadley, Nick; Elliot, David; Whyte, Ian Boyd; Kettle's Yard, Cambridge; De La Warr Pavilion, Bexhill-on-Sea (Cambridge : Kettle's Yard Cambridge, 2010)
Afnah, Maliheh ; Anastasi, William ; Auerbach, Frank ; Belmar, Andrés ; Beuys, Joseph ; Bishop, James ; Boccioni, Umberto ; Bomberg, David ; Bourgeois, Louise ; Brisley, Stuart et al.
Modern Times Responding to chaos, Kettle's Yard, Cambridge, 16 January - 14 March 2010 / De La Warr Pavilion, Bexhill-on-Sea, 1 April - 13 June 2010
kunstcatalogus